Глиссирование и полет над экраном у животных - Кистяковский, А.Б. (Вестник зоологии, 1967)
Some vertebrates use peculiar forms of movement. To speed up the take-off of the flying fishes of the genera Exocoetus, Cypselurus and others, gliding was applied. This form of movement is also met in various waterfowls. Development course in duckling feathering provides application of gliding before acquiring the ability to flight. Flight over the screen by the use of increased lift is mostly typical for the flying fishes; under certain conditions the birds of other orders are flying in the same manner, the water surface being as a screen. This bird flight is distinguished by the increasing of frequency of wing-beat and decreasing of their amplitude and increasing of the speed.